2015
DOI: 10.1037/cdp0000025
|View full text |Cite
|
Sign up to set email alerts
|

Examining the psychometric validity of the Multigroup Ethnic Identity Measure-Revised (MEIM-R) in a community sample of African American and European American adults.

Abstract: The purpose of this study was to examine the psychometric properties of the Multigroup Ethnic Identity Measure-Revised (MEIM-R), focusing on a sample drawn from a geographic region in the United States that has not been included in previously published research on the MEIM-R. Data were obtained from a community-based sample of 105 African American (AA) and 91 European American (EA) adults located in the state of Alabama. The MEIM-R was best represented by two constructs-exploration and commitment. AA adults re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…In a context such as Sicily for Tunisians, where adolescents have different opportunities to have contact with both their heritage and the mainstream culture, exploratory behaviors are allowed by the family and the larger society, becoming the resources through which Tunisian youth learn about the history, traditions, and customs of their group in order to reach a clear understanding of the meaning of their ethnicity in terms of commitment. In this perspective, as many scholars noted, EIE is a kind of prerequisite for perceiving a sense of belonging to an ethnic group during adolescence (Chakawa, Butler, & Shapiro, 2015;Phinney & Ong, 2007;Syed & Azmitia, 2010). This is well known by authors involved in ego identity research who have stressed the importance of the exploration process for the development of personal identity, and, consequently, for an individual's well-being (Crocetti et al, 2008;Luyckx, Goossens, & Soenens, 2006).…”
Section: Eie Eic and Acculturative Stressmentioning
confidence: 89%
“…In a context such as Sicily for Tunisians, where adolescents have different opportunities to have contact with both their heritage and the mainstream culture, exploratory behaviors are allowed by the family and the larger society, becoming the resources through which Tunisian youth learn about the history, traditions, and customs of their group in order to reach a clear understanding of the meaning of their ethnicity in terms of commitment. In this perspective, as many scholars noted, EIE is a kind of prerequisite for perceiving a sense of belonging to an ethnic group during adolescence (Chakawa, Butler, & Shapiro, 2015;Phinney & Ong, 2007;Syed & Azmitia, 2010). This is well known by authors involved in ego identity research who have stressed the importance of the exploration process for the development of personal identity, and, consequently, for an individual's well-being (Crocetti et al, 2008;Luyckx, Goossens, & Soenens, 2006).…”
Section: Eie Eic and Acculturative Stressmentioning
confidence: 89%
“…The scale measures ethnic identity, with higher scores indicating a more achieved ethnic identity (Phinney & Ong, 2007). Studies in the United States (Brown et al, 2014;Burrow-Sanchez, 2014;Chakawa et al, 2015;Yoon, 2011) as well as Canada, Italy and Bulgaria (Homma et al, 2014;Musso et al, 2017;Phinney & Ganeva, 2011) have supported the correlated two-factor structure. Other studies have used the MEIM-R beyond replication, such as in Tanzania with various tribes such as Chagga, Massai and Nyakyusa (Drescher et al, 2017), in New Zealand with New Zealand Pākehā (those of British or European ancestry), Chinese, Samoan and Māori (indigenous) groups (Webber et al, 2013).…”
Section: Multigroup Ethnic Identity Measure-revised (Meim-r)mentioning
confidence: 94%
“…Because certain research has also indicated that ethnic identity acts as a protective factor against thin ideals, this could further compound the effect. As previously stated, African-American women tend to feel more strongly attached to their ethnic identity than women from other ethnic groups; 11,12 however, it is unclear to what degree this attachment is positively or negatively associated with motivation for engaging in a healthy lifestyle. Understanding the unique impact of identity and its relation to engagement in health behaviors is crucial in a population that experiences some of the worst health outcomes in a variety of areas, such as rates of obesity and diabetes.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, African-American women tend to feel more strongly attached to their ethnic identity than European American women. 11,12 The level of identification with one's ethnicity can impact multiple facets of life, especially if one strongly identifies with their ethnicity.…”
Section: Introductionmentioning
confidence: 99%